Slavery and historical capitalism during the nineteenth century - Tomich, Dale W., 1946- (Lexington Books, an imprint of Rowman and Littlefield Publishing Group, Incorporated, 2017)
This collection examines slavery and its relationship to international capital during the nineteenth century. With thematic chapters and case studies written by an international array of contributors, this volume analyzes the historiography of Atlantic slavery and investigates the slave economies of the US South, Cuba, and Brazil.